Sulfonamide resistance genes in soils treated with waste from animal production in an organic production system - Oliveira, Camila Costa de; Bertholoto, Danielli Monsores; Nascimento, Elisamara Caldeira do; Zonta, Everaldo; Coelho, Shana de Mattos de Oliveira; Souza, Miliane Moreira Soares de; Melo, Paulo Regis Bandeira; Coelho, Irene da Silva (Semina: Ciências Agrárias, 2021)
Animal waste is widely used in organic production systems. However, these residues can increase antimicrobial determinants in the soil. In this perspective, this study was developed to evaluate the presence of sulfonamide resistance genes in soils from an organic production system that received animal waste as organic fertilizer. Soil samples were collected from four properties with different management practices to increase soil fertility. Three properties use the animal waste from the conventional system and the other use plant residues as soil cover and a legal reserve. The extraction of total DNA from soil was carried out followed by the amplification of genes encoding sulfonamide resistance (sul1 and sul2) by the PCR (polymerase chain reaction) technique. The sul1 and sul2 genes were detected only in soils treated with animal waste. The genes were not detected in soils from the legal reserve and the property that used plant residues as soil cover. These results indicate that the use of animal waste as agricultural fertilizer can increase genes for resistance to antimicrobials in the soil and the composting process may not be enough to eliminate them. This information reiterates the need to implement standards that establish quality parameters for animal waste, considering resistance to antimicrobials, as well as the development of management strategies that reduce the risk of spreading resistance to antimicrobials when these residues are applied to soils.